Human autoimmune diseases: a comprehensive update - Wang, Lifeng; Wang, Fu‐Sheng; Gershwin, M. Eric (Journal of internal medicine, 2015)
There have been significant advances in our understanding of human autoimmunity that have led to improvements in classification and diagnosis and, most importantly, research advances in new therapies. The importance of autoimmunity and the mechanisms that lead to clinical disease were first recognized about 50 years ago following the pioneering studies of Macfarlane Burnett and his Nobel Prize‐winning hypothesis of the ‘forbidden clone’. Such pioneering efforts led to a better understanding not only of autoimmunity, but also of lymphoid cell development, thymic education, apoptosis and deletion of autoreactive cells. Contemporary theories suggest that the development of an autoimmune disease requires a genetic predisposition and environmental factors that trigger the immune pathways that lead, ultimately, to tissue destruction. Despite extensive research, there are no genetic tools that can be used clinically to predict the risk of autoimmune disease. Indeed, the concordance of autoimmune disease in identical twins is 12–67%, highlighting not only a role for environmental factors, but also the potential importance of stochastic or epigenetic phenomena. On the other hand, the identification of cytokines and chemokines, and their cognate receptors, has led to novel therapies that block pathological inflammatory responses within the target organ and have greatly improved the therapeutic effect in patients with autoimmune disease, particularly rheumatoid arthritis. Further advances involving the use of multiplex platforms for diagnosis and identification of new therapeutic agents should lead to major breakthroughs within the next decade.